2021
DOI: 10.14309/ajg.0000000000001202
|View full text |Cite
|
Sign up to set email alerts
|

The Perils and Pitfalls of Esophageal Dysmotility in Idiopathic Pulmonary Fibrosis

Abstract: Introduction: Gastroesophageal reflux plays a significant role in idiopathic pulmonary fibrosis (IPF).Given the morbidity and mortality associated with IPF, understanding the mechanisms responsible for reflux is essential if patients are to receive optimal treatment and management, especially given the lack of clear benefit of anti-reflux therapies. Our aim was to understand the inter-relationships between esophageal motility, lung mechanics and reflux (particularly proximal reflux -a prerequisite of aspiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
(58 reference statements)
1
13
0
Order By: Relevance
“…As to the relationship between motility alterations leading to GER and the potential development of idiopathic pulmonary fibrosis (IPF), Gao et al 44 found that patients with this complication presented with lower LES and UES, higher prevalence of hypotensive LES and hiatal hernia (HH), and combined impedance showed that 46.4% of them had weak peristalsis and the bolus transit was impaired. A recent study 45 using this sophisticated HRIM has shown a significantly higher rate of IEM in IPF patients than in controls and this motor abnormality was associated with more proximal reflux and worse pulmonary function tests in the former population, thus corroborating the pathogenetic role of esophageal dysmotility in this group of ILD patients, similar to what may occur in SSc patients.…”
Section: Data From High‐resolution Impedance Manometry (Hrim) In Syst...supporting
confidence: 58%
See 1 more Smart Citation
“…As to the relationship between motility alterations leading to GER and the potential development of idiopathic pulmonary fibrosis (IPF), Gao et al 44 found that patients with this complication presented with lower LES and UES, higher prevalence of hypotensive LES and hiatal hernia (HH), and combined impedance showed that 46.4% of them had weak peristalsis and the bolus transit was impaired. A recent study 45 using this sophisticated HRIM has shown a significantly higher rate of IEM in IPF patients than in controls and this motor abnormality was associated with more proximal reflux and worse pulmonary function tests in the former population, thus corroborating the pathogenetic role of esophageal dysmotility in this group of ILD patients, similar to what may occur in SSc patients.…”
Section: Data From High‐resolution Impedance Manometry (Hrim) In Syst...supporting
confidence: 58%
“…As to the relationship between motility alterations leading to GER and the potential development of idiopathic pulmonary fibrosis (IPF), Gao et al 44 found that patients with this complication presented with lower LES and UES, higher prevalence of hypotensive LES and hiatal hernia (HH), and combined impedance showed that 46.4% of them had weak peristalsis and the bolus transit was impaired. A recent study 45…”
Section: Data From Hi G H -Re Soluti On Impedan Ce Manome Try (Hrim) ...mentioning
confidence: 98%
“…[38] Reflux events generally occur during inspiration and are inversely correlated with inspiratory thoracic pressures. [9] [10] Other mechanical factors that might contribute to GERD secondary to IPF are reduced esophageal body motility, lower basal lower esophageal sphincter pressure, and delayed gastric emptying. [36] We therefore investigated the possibility of causality in both directions using a bidirectional MR approach, but we found no evidence of a causal effect of IPF on GERD risk.…”
Section: Discussionmentioning
confidence: 99%
“…[8] This is plausible given that reduced lung compliance in IPF can lead to more negative intrathoracic pressures and reflux events are inversely correlated with inspiratory thoracic pressures. [9,10] Unlike observational associations, genetic associations are not affected by classical confounding or reverse causation, as genes are randomly allocated at conception. A Mendelian randomisation (MR) approach that uses genetic variants known to affect GERD as its proxies (instrumental variables) can therefore provide indirect evidence for a causal effect of GERD on the risk of IPF, if its underlying assumptions hold.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation